Providing independent-learning space to promote English learners’ self-regulation - Cendra, Anastasia Nelladia; Wijaya, Alberik Ryan Tendy (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2024)
Independent learning is a powerful way to enhance English mastery. Yet, its effect on self-regulation is not yet explored further. This research investigated that matter by answering the following questions: 1) How is the independent learning activity per-ceived by English learners? 2) Can independent learning activities assist English learners in developing self-regulation skills? Twenty-nine university-level English learners participated in this qualitative-descriptive research which uses an open-ended questionnaire and interview. This study showed that independent learning is perceived positively by the participants. They mentioned that independent learning gave them more chances to understand the materials. Furthermore, they believed that the main outcome of independent learning was the increase in their English skills. For them, the enhancement on the self-regulation skills became a secondary outcome. As such, while independent learning has the potential to enhance learners’ self-regulation skills, the participants believed that they did not really grasp the concept of self-regulation and how independent learning would promote it. Thus, it is suggested that the learners must first be familiar with the concept of self-regulation and how inde-pendent learning can enhance self-regulation skills. This concept, therefore, must be promoted first by the teachers before independent learning activities are carried out.